Damage Probability Matrices and Empirical Fragility Curves From Damage Data on Masonry Buildings After Sarpol-e-zahab and Bam Earthquakes of Iran - Biglari, Mahnoosh; Formisano, Antonio (Frontiers in Built Environment, 2020)
The weakness of tensile strength and high weight in masonry structures under the dynamic loads of earthquakes have always led to structural damage, financial losses, injuries and deaths. In spite of the cheap and affordable masonry materials, it has been very limited their use in constructions over the past three decades. However, common masonry materials are still found in monumental and historical structures, deteriorated texture and rural buildings. Identifying the seismic behaviour and the probability of the structural damage is vital for pre-earthquake seismic risk reduction of urban areas and the rapid post-earthquake assessment. The earthquake event occurred in Ezgeleh on 2017 November 12th with Mw=7.3 triggered the greatest damage in the Sarpol-e-zahab city at a distance of about 37 kilometres from the epicentre. Post-earthquake reconnaissance, microtremor analysis and rapid visual inventory of structural damages in different zones were performed by the research teams. In the present study, the strong ground motion, the peak ground acceleration and its corresponding intensity distribution, which are based on the site response analysis in different parts of the city, are introduced. Afterward, damage probability matrices of different types of masonry buildings, namely unreinforced masonry and confined masonry buildings, are determined for both bins of peak ground accelerations and intensities. Finally, the fragility curves of two types of masonry structures are extracted based on RISK-UE level 1 (LM1) method by assuming beta distribution to estimate the probability distribution function of the damage. These curves are useful in assessing pre-earthquake possible damages in masonry structures with similar construction methods and similar materials to reduce seismic risks.